Prevention of Periodontal Pocket Formation after Mandibular Third Molar Extraction Using Dentin Autologous Graft: A Split Mouth Case Report. (31st August 2020) - De Biase, Alberto; Mazzucchi, Giulia; Di Nardo, Dario; Lollobrigida, Marco; Serafini, Giorgio; Testarelli, Luca
Abstract : Surgical extraction of the third molar can often result in the development of a periodontal pocket distal to the second molar that could delay the healing, and the socket could be colonized by bacteria and lead to secondary abscesses, or it may cause mobility or hypersensitivity. The aim of this case report is to assess the efficacy of a dentin autograft in the prevention of periodontal dehiscences after the surgical extraction of the third molar, obtained by the immediate grinding of the extracted tooth. A healthy 18-year-old male patient underwent surgery of both impacted mandibular molars: right postextractive socket was filled with grinded dentin; then, the left one was filled with fibrin sponge. The patient was followed up for six months, and clinical and radiographic assessment were performed: measurements of plaque index (PI), bleeding on probing (BOP), gingival index (GI), clinical attachment level (CAL), and probing pocket depth (PPD) were done before surgery and repeated at 90 and 180 days after the extractions. Measurements made at six months after the surgery revealed that the grafted site was characterized by a minor depth of the pocket if compared with the nongrafted site, with no clinical/radiographic signs of complications.